Bt-cotton and secondary pests. (19th May 2008) - Wang, Shenghui; Just, David R.; Pinstrup-Andersen, Per
Bt-cotton seed has been effective to control the damage of bollworm in Chinese cotton production since 1999, reducing the need for pesticides and increasing incomes of Chinese farmers. Field data collected in 2004 indicates that these benefits have been eroded by increasing the use of pesticides aimed to control secondary pests. The combination of Bt-cotton seed and other forms of biological pest control may help farmers regain the economic and environmental benefits of previous years. Failure to find a solution, may lead to the discontinuation of the use of Bt-cotton seed in China and elsewhere.